Immunodeficiencies in chronic muco-cutaneous candidosis - Lehner, T. (1972)
Cell-mediated and humoral immune responses have been investigated in fifteen patients with chronic muco-cutaneous candidosis and appropriate controls. An impaired cellular response to Candida albicans was found in all patients by the cytotoxicity test, using specifically activated lymphocytes which were reacted against (51)Cr labelled chicken red cells. Migration of guinea-pig macrophages was not inhibited by supernatants from stimulated leucocyte cultures in eleven out of twelve patients and similar results were found when these patients were skin tested for delayed hypersensitivity. A significant though low grade lymphocyte transformation reaction was detected in five patients, two of whom yielded a negative delayed skin reaction. Responses to unrelated antigens, such as PPD and Herpesvirus hominis Type 1 were also impaired in some patients but to a lesser extent than to Candida albicans. It is suggested that chronic muco-cutaneous candidosis shows a spectrum of increasing cell-mediated immunodeficiencies which can be ranked into six grades. Chronic oral candidosis has a limited cellular immune defect (Grades A, B and C) whereas in the muco-cutaneous candidosis a more severe immunodeficiency is found (Grades D, E and F). Serum IgG and IgM antibodies to Candida were largely impaired in all but one grade of immunodeficiency (Grade E), whereas salivary IgA antibodies were deficient in the three more severe grades of immunodeficiencies (D, E and F).